Land Use Change Effect on Soil Carbon Stock and Selected Soil Properties in Gobu Sayyo District, Western Ethiopia - Deginet Wako; Mengistu Welemariam; Getahun Kitila (The Scientific World Journal)
Land use change is one of the major factors affecting soil degradation. Growing population pressure has increased land use change with more negative effects on soil carbon storage and overall soil properties. The objective of this study was to assess the effect of land use changes on soil organic carbon (SOC) stock and selected soil physicochemical properties in Gobu Sayyo, Western Ethiopia. Soil samples were collected from three adjacent land uses, that is, forest land, grazing land, and cultivated land, at 0–20 and 20–40 cm soil depths. A total of 36 composite soil samples were collected, and the major soil properties and SOC storage of the area were analyzed and computed based on their standard procedures. SOC stock was significantly (p<0.05) higher (43.09–81.86 t ha−1) in forest land and was significantly lower (38.08–43.09 t ha−1) in cultivated land at the top 20 cm. SOC stock decreased with depth in all land uses. Changes in land use and soil depth affected the physical and chemical properties of soil. The physical soil property such as bulk density (BD) was higher (1.62 g cm−3) in the cultivated land, whereas the lowest (1.08 g cm−3) was recorded in the forest at 0–20 cm depth. Comparatively, the moisture content was higher (25.89%) under forest land at the depth of 20–40 cm and was lower (11.22%) under cultivated land. The chemical soil properties like exchangeable Ca2+, Mg2+, and K+ were higher in forest lands. Organic carbon, available phosphorus (AvP), total nitrogen (TN), exchangeable calcium (ex.Ca2+), exchangeable magnesium (ex.Mg2+), exchangeable potassium (ex.K+), and cation exchange capacity (CEC) were lower under cultivated lands. pH increased with depth and was higher under forest land and lower under cultivated land. Soils of the study area are in general acidic to slightly acid, with pH values ranging from 4.6 to 6.02. The pH, SOC, TN, AvP, and CEC were higher under forest land compared to cultivated and grazing lands. It can be concluded that SOC stocks and the physical and chemical properties were affected by land use change and depth. Therefore, reducing the intensity of cultivation, adopting integrated soil fertility management, and maintaining forest land must be practiced to save the soil of the area from degradation.